Oreocharis synergia, a new species of Gesneriaceae from Northwestern Yunnan, China - Chen, Wen-Hong; Möller, Michael; Chen, Run-Zheng; Rui, Rong-Ju; Shui, Yu-Min (Phytotaxa, 2015)
A new species of Oreocharis (Gesneriaceae) from southwestern Yunnan, China, Oreocharis synergia is described and illustrated. The diagnostic characteristics are given with a comparison with its most similar species, Oreocharis bodinieri.